THE ROLE OF THE TEACHER IN GENDER EDUCATION OF THE CHILD IN THE CONTEXT OF THE CONCEPT OF TEACHER EDUCATION DEVELOPMENT - Зубко, Ольга (SWorldJournal, 2024)
The article outlines the problematic field of educational reforms in the context of the Concept of Development of Pedagogical Education and Integration with the European Educational Space. The main areas of research on gender issues are highlighted. It i